Désiré-Magloire Bourneville and his contributions to pediatric neurology - Mariana Teresa Gómez-López; Leonardo Palacios-Sánchez; Alberto Vélez van Meerbeke; Juan Sebastián Botero-Meneses (Arquivos de Neuro-Psiquiatria)
ABSTRACT Désiré-Magloire Bourneville ought to be thought of as the father of Pediatric Neurology for his significant contributions to the field. He worked as a physician, politician, writer, and editor. He was the first to describe the autosomal dominant genetic condition known as “tuberous sclerosis complex”, after conducting an autopsy on a young female patient, where the main finding in the central nervous system was multiple dense tubers. The patient had refractory epilepsy and intellectual disability. His work was based on the study of epilepsy and idiocy, and he was also an advocate of public health and social medicine education; creating day hospital programs for children with this type of neurologic disease.